Rebuilding the Fortymile caribou herd: A model of cooperative management planning - Gronquist, Ruth M.; Haynes, Terry L.; Gardner, Craig L. (Rangifer, 2005)
We examined the public process used to develop the 1996—2001 Fortymile Caribou (Rangifer tarandus) Herd Management Plan adopted by state and federal management boards. The process differed from most government-supported planning processes because it was initiated by residents of Alaska and Yukon, and not by an agency. State, federal, and territorial agencies were asked to participate in and support development of a management plan that would include a broad range of interest groups. We describe the planning effort, issues addressed by the planning team that posed significant challenges during both the planning and implementation phases, and then identify unforeseen costs and benefits derived from the process. Critical decision points in plan development and implementation are discussed.